Performance of Islamic banks versus conventional banks in terms of profitability, leverage and liquidity ratios in Malaysia / Hafidzah Abd Azis - Abd Azis, Hafidzah (2006)
The study evaluates inter temporal and interbank performance of Islamic banking and conventional banks in terms of profitability, liquidity and also leverage ratios for ten selected banks. There are five from Islamic banks and another five from conventional banks in Malaysia. The five selected Islamic banks are Bank Islam Malaysia Berhad, Am lslamic Bank Berhad, Bank Muamalat Malaysia Berhad, Hong Leong Islamic Bank Berhad and RHB Islamic Bank Berhad. Then, another five banks from conventional banks are Malayan Banking Berhad, Bumiputra-Commerce Bank Berhad, Ambank (M) Berhad, Public Bank Berhad and RHB Bank Berhad. Then, the period selected from year 2000 until 2005. Financial ratios are applied in measuring these performances and their income statement and balance sheets is used. T-test used in determining their significance. By making this research, researcher can find the objectives of this topic that are to study about the performance of Islamic banks comparing to conventional banks in terms of their liquidity, leverage and also profitability ratios, to find which types of banks performed better between two banks; Islamic and conventional banks and to make a comparing of ratio analysis in Islamic bank and conventional bank.